Studies on Drug – Human Serum Albumin Binding: The Current State of the Matter - D. Zhivkova, Zvetanka (Current Pharmaceutical Design, 2015)
Human serum albumin (HSA) is the major plasma protein with vital functions acting as depot and career for many endogenous (fatty acids, bilirubin, etc.) and exogenous substances (drugs, nutrients, etc.) in the blood. Binding to HSA controls the free, active concentration of the drug and may affect considerably the overall pharmacodynamic and pharmacokinetic profile. Studies on drug – protein binding are important from both theoretical and practical point of view as they allow better understanding of the processes underlying drug disposition and elimination and the effect of several pathological states or co-administered drugs on drug delivery and efficacy. The present review focuses on the current state of drug – HSA binding studies. The major functions and consequences of drug – protein binding are described. The X-ray structure of HSA is discussed focusing on the location and the architecture of the primary drug and fatty acids binding sites. Some of the most commonly used methods for drug – HSA binding assay are presented together with examples for their application. The most extensive studied topics in the area are discussed including quantitative characterization of drug – HSA complexation, identification of the binding sites, stereoselectivity of drug – HSA interactions, and thermodynamic characterization of the binding process. A short section is devoted to in silico prediction of drug – HSA binding as an important step in drug design and development.
Keywords: stereoselective binding